2021
DOI: 10.1088/1475-7516/2021/03/059
|View full text |Cite
|
Sign up to set email alerts
|

Natural inflation with a nonminimal coupling to gravity

Abstract: Although natural inflation is a theoretically well-motivated model for cosmic inflation, it is in tension with recent Planck cosmic microwave background anisotropy measurements. We present a way to alleviate this tension by considering a very weak nonminimal coupling of the inflaton field to gravity in both contexts of metric and Palatini formulations of general relativity. We start our discussions with a generic form of the inflaton coupling to the Ricci scalar, then focus on a simple form to do phenomenologi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…for comparative purposes we we reproduce the results of ref [10] The effect of adding the term αR 2 can be realized in figure (4b). The same domain for the parameters f and ξ are scanned but now for non-zero α = 0.1.…”
Section: Comparative Analysis With Observationmentioning
confidence: 83%
See 1 more Smart Citation
“…for comparative purposes we we reproduce the results of ref [10] The effect of adding the term αR 2 can be realized in figure (4b). The same domain for the parameters f and ξ are scanned but now for non-zero α = 0.1.…”
Section: Comparative Analysis With Observationmentioning
confidence: 83%
“…On the other hand, current observational constraints on non-minimal coupling are pretty loose, for example|ξ| ≥ 10 15 from the LHC's result [9]. NI with NMC to gravity has been studied [10], The study shows that this extension can bring natural inflation's predictions into good agreement with Planck data, Depending on values of the coupling constant ξ and the symmetry breaking scale f .…”
Section: Introductionmentioning
confidence: 99%
“…There are several other attempts to bring natural inflation into agreement with Planck results, such as with a warm dissipative effect [53], or other forms of modified gravity, e.g., in a UV complete quadratic gravity [54], a non-minimal coupling to Ricci scalar [29], f (R, T ) gravity [33]. It is worth noticing that the simple form of f (R, T ) considered in Ref.…”
Section: Natural Inflationmentioning
confidence: 97%
“…A natural question then arises: Is it possible to reconsider those inflationary models that have been ruled out by observations after assuming that the inflaton fields are non-minimally coupled to gravity? Some indications toward a positive answer have been put forward in the literature [24,25,26,27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…In the observational perspective, it has also been shown that in some cases the introduction of a non-minimal coupling may improve the description of the data (see e.g. [24][25][26][27][28][29][30][31][32] and references therein).…”
Section: Introductionmentioning
confidence: 99%